2021
DOI: 10.1200/go.21.00013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Smartphone-Based Cervical Cancer Screening Among HIV-Positive Women in Western Kenya

Abstract: PURPOSE Adjunct cervical cancer screening methods are under evaluation to improve the diagnostic accuracy of human papillomavirus (HPV)-based screening in low- and middle-income countries. We evaluated the feasibility and acceptability of smartphone-based cervicography among HPV-positive women living with HIV (WLWH) in Western Kenya. METHODS HPV-positive WLWH of 25-49 years of age enrolled in a clinical trial (ClinicalTrials.gov identifier: NCT04191967 ) had digital images of the cervix taken using a smartphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Thirteen studies enrolled WLHIV attending cervical cancer screening in outpatient gynaecology clinics, 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 whereas 21 studies recruited WLHIV attending HIV clinics. 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Two studies recruited WLHIV with a prior positive screen-test (HPV-positive) 58 , 59 and two studies included a combination of women attending primary care and women referred to colposcopy because of positive HPV test and/or abnormal cytology. 60 , 61 The median age of enrolled women within studies ranged from 30 to 50 years (age range: 19 to 68 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies enrolled WLHIV attending cervical cancer screening in outpatient gynaecology clinics, 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 whereas 21 studies recruited WLHIV attending HIV clinics. 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Two studies recruited WLHIV with a prior positive screen-test (HPV-positive) 58 , 59 and two studies included a combination of women attending primary care and women referred to colposcopy because of positive HPV test and/or abnormal cytology. 60 , 61 The median age of enrolled women within studies ranged from 30 to 50 years (age range: 19 to 68 years).…”
Section: Resultsmentioning
confidence: 99%
“… c ART status not reported for 9 studies. d Studies enrolling WLHIV with a prior positive screen-test (HPV-positive) 58 , 59 and two studies included a combination of women attending primary care and women referred to colposcopy because of positive HPV test and/or abnormal cytology. 60 , 61 excluded from pooled estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded improved training support and better communication with patients for targeted education improve adherence ( Asgary et al, 2019 ). Similarly, in a 2018 study by Quercia et al, using a smartphone reported that DC helped HCWs with decision making and management options, including image sharing during the time of referral ( Mungo et al, 2021 ). Using same-day screen-and-treat models was also demonstrated in many studies.…”
Section: Resultsmentioning
confidence: 99%
“…Extended HPV genotyping, viral and host methylation of genes, dual staining for p16/Ki67, and detection of viral oncoproteins E6/E7 are examples of promising approaches to further identify HPV positive women at highest risk of cervical cancer [31,32]. An additional approach currently under evaluation that may be especially suited for low-cost point-of-care screening in LMIC settings combines advances in digital images captured by a smartphone [33] or other dedicated device with the automated reading and scoring of cervical cancer risk through the application of artificial intelligence algorithms to cervical cancer images [34]. Preliminary data suggests this automated visual evaluation (AVE) approach demonstrates high performance when using high quality images such as cervigram images [35,36].…”
Section: Considerations For Selecting Cervical Cancer Screening and T...mentioning
confidence: 99%